The Anagyrus (Hymenoptera: Encyrtidae) parasitoids of the obscure mealybug Pseudococcus viburni (Hemiptera: Pseudococcidae) in Spain, with description of a new species - Soler, José María; Falcó-Garí, José Vicente; Herrero, Berta; Aquino, Daniel Alejandro (Zootaxa, 2021)
The presence of three species of the genus Anagyrus Howard (Hymenoptera: Encyrtidae) parasitizing the obscure mealybug Pseudococcus viburni (Signoret) (Hemiptera: Pseudococcidae) in agricultural ecosystems of citrus, persimmon and ornamental plants from Eastern Spain is recorded. Anagyrus aligarhensis Agarwal & Alam is recorded for the first time as parasitoid on this mealybug. Anagyrus fusciventris (Girault) is a new record for Spain. Anagyrus borrianensis sp. nov., reared as a specific primary parasitoid of this mealybug, is described and illustrated. The joint presence of Anagyrus pseudococci (Girault) and Anagyrus vladimiri Triapitsyn on citrus crops is confirmed. A key to species of Anagyrus parasitoids of Planococcus and Pseudococcus mealybugs in Eastern Spain is provided